State-level policies and receipt of CDC-informed opioid thresholds among commercially insured new chronic opioid users - Calabrese, Martin J.; Shaya, Fadia T.; Palumbo, Francis; McPherson, Mary Lynn; Villalonga-Olives, Ester; Zafari, Zafar; Mutter, Ryan (Journal of Opioid Management, 2024)
Objectives: To evaluate the association of state-level policies on receipt of opioid regimens informed by Centers for Disease Control and Prevention (CDC) morphine milligram equivalent (MME)/day recommendations. Design: A retrospective cohort study of new chronic opioid users (NCOUs). Setting: Commercially insured plans across the United States using IQVIA PharMetrics® Plus for Academics database with new chronic use between January 2014 and March 2015. Participants: NCOUs with ≥60-day coverage of opioids within a 90-day period with ≥30-day opioid-free period prior to the date of the first qualifying opioid prescription. Interventions: State-level policies including Prescription Drug Monitoring Program (PDMP) robustness and cannabis policies involving the presence of medical dispensaries and state-wide decriminalization. Main outcome measures: NCOUs were placed in three-tiered risk-based average MME/day thresholds: low (>0 to <50), medium (≥50 to <90), and high (≥90). Multinomial logistic regression was used to estimate the association of state-level policies with the thresholds while adjusting for relevant patient-specific factors. Results: NCOUs in states with medium or high PDMP robustness had lower odds of receiving medium (adjusted odds ratio [AOR] 0.74; 95 percent confidence interval [CI]: 0.62-0.69) and high (AOR 0.74; 95 percent CI: 0.59-0.92) thresholds. With respect to cannabis policies, NCOUs in states with medical cannabis dispensaries had lower odds of receiving high (AOR 0.75; 95 percent CI: 0.60-0.93) thresholds, while cannabis decriminalization had higher odds of receiving high (AOR 1.24; 95 percent CI: 1.04-1.49) thresholds. Conclusion: States with highly robust PDMPs and medical cannabis dispensaries had lower odds of receiving higher opioid thresholds, while cannabis decriminalization correlated with higher odds of receiving high opioid thresholds.